Diatomáceas como bioindicadoras em estudo de longa duração na planície de inundação do alto rio Paraná. - Osório, Nicolli Cristina (2021)
Freshwater ecosystems such as the Upper Paraná River floodplain are constantly subjected to environmental changes caused by natural disturbances, but mainly by anthropogenic impacts (such as dams), which have drastically affected the biodiversity of these aquatic systems. One way to assess the rates of environmental change in systems such as plains is through biomonitoring studies on large temporal scales, with diatoms being excellent bioindicators in determining environmental changes in different aquatic ecosystems. Based on this, the temporal pattern of the periphytic diatom community of a lake in the upper Paraná River floodplain was investigated in order to seek patterns that reflect the environmental changes in this plain, covering studies with different approaches, such as ecology, taxonomic and of environmental education. As a result of these different studies, it is noteworthy that the association of the taxonomic and functional approach in the components of beta diversity was extremely important for the interpretation of variation in the composition of diatom species in a long time series, especially when considering the importance of the contribution beta diversity site - LCBD. It was also sought to highlight the use of diatoms as indicators in determining hydrological changes, reinforcing the need for continuous monitoring of the region, in order to follow the direction of ecological changes, both hydrological and climatic in this plain. The importance of taxonomic studies in the plain was also highlighted in this thesis, in order to better understand the local biodiversity of diatoms, since new species such as Staurosirella paranaensis are being registered. Finally, this thesis includes a proposal for educational games on microalgae and their ecological importance in the environmental indication of aquatic bodies, to emphasize the relevance of environmental education in the research, teaching and extension process.